When 'Being There' Is Disallowed: Disruptions to Knowing and Caring During COVID-19 Visitor Restrictions. Issue 1 (2nd January 2022) - Sinding, Christina; Cape, Susan; Charles, Lyndsey; Gosselin, Claire; Kettings, Matthew; Taniguchi, Alan; Willison, Kathleen Baba
Abstract: This qualitative study explored the accounts of five health professionals working in hospitals in Hamilton, Ontario, Canada who provided end-of-life care during the COVID-19 pandemic. The study goal was to understand how palliative care providers experienced and responded to the significant change in family presence when visitors were restricted to slow the spread of the virus. Identified was the loss and disruption of important forms of knowing including observational and embodied knowing. Family members' knowledge of how their person was faring was curtailed, as was providers' capacities to know families personally. Family members' less obvious needs did not come forward as readily in the absence of informal encounters with providers. Constraints on knowing and embodied actions often meant phone and video meetings failed to provide meaningful connection. Providers adapted their practice in a range of ways, including by offering verbal and visual images of the person in the setting, paying attention differently, and conveying to family members their knowledge of patients as individuals. The changes and challenges health providers remarked on and the ways they adapted and extended themselves reveal in a new way how the regular presence of family in the care setting shapes the quality of end-of-life care.